1995
DOI: 10.1016/0014-5793(95)00790-g
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and processing mechanisms of procathepsin L in bone resorption

Abstract: Secretion of procathepsin L into the culture medium from a bone cell mixture was markedly enhanced by addition of parathyroid hormone (PTH), 1 a,25-(OH)2D 3 or tumor necrosis factor a (TNFa). These stimulators of secretion of procathepsin L enhanced bone pit formation, which was inhibited by E-64, but not by CA-074, a specific inhibitor of cathepsin B. Procathepsin L may thus participate in the process of bone collagenolysis during bone resorption. Procathepsin L partially purified from rat long bones under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 19 publications
(19 reference statements)
2
25
0
Order By: Relevance
“…However, it has been reported that secreted cathepsin L plays a major role in the process of bone resorption by osteoclasts (Kakegawa et al, 1993(Kakegawa et al, , 1995. In this experiment, we clearly demonstrated that the level of secreted procathepsin L was correlated with the capability of bone invasion of the cancer cells.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…However, it has been reported that secreted cathepsin L plays a major role in the process of bone resorption by osteoclasts (Kakegawa et al, 1993(Kakegawa et al, , 1995. In this experiment, we clearly demonstrated that the level of secreted procathepsin L was correlated with the capability of bone invasion of the cancer cells.…”
Section: Discussionsupporting
confidence: 64%
“…Procathepsin L secreted from BHY cells may be in a free form, because BHY cells secreted only a trace level of TIMP1. Procathepsin L was reported to be activated in acidic conditions (Kakegawa et al, 1995). Therefore, procathepsin L secreted from BHY cells may be easily activated at the front of bone invasion, and the activated cathepsin L might degrade the demineralized bone matrix (mainly composed of type-I collagen).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is translated as preprocathepsin L, which is then processed to procathepsin L with a molecular mass of 39 kDa and further processed to the mature cathepsin L, which exists in either singlechain (30 kDa) or two-chain (25 and 5 kDa) forms (9, 20 -22). Cathepsin L is suggested to participate in turnover of intracellular or endocytosed proteins (8), degradation of ECM proteins, antigen processing and presentation (23), bone resorption (24,25), and various other processes. Many growth factors and oncogenes can stimulate cathepsin L expression (26 -29), and increased expression of cathepsin L is commonly associated with malignant transformation (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been implicated in a range of processes including turnover of proteins involved in growth regulation, tumor invasion and metastasis (21), and bone resorption (22). The mouse analogue of procathepsin is secreted from transformed mouse fibroblasts and has been at first called major excreted protein (11).…”
mentioning
confidence: 99%